Acacia hybrid: Ecology and silviculture in Vietnam - Chaw, C.S.; Mitlöhner, Ralph (Center for International Forestry Research, 2011)
This manual summarises information on the ecology and silviculture of the species Acacia hybrid, with an emphasis on Vietnam. It also encompasses growth and yield data from published sources, as well as collected from sites under smallholder industrial plantations in Binh Dinh Province, Vietnam. This manual is 1 of 5 that guide smallholder tree planting of five selected tree species in Vietnam. The other four species are: Acacia mangium Willd, Cinnamomum parthenoxylon (Jack) Meisn, Erythrophloeum fordii Oliver and Eucalyptus urophylla S.T. Blake.